1991
DOI: 10.1002/pros.2990190202
|View full text |Cite
|
Sign up to set email alerts
|

Relation of endocrine‐paracrine cells to cell proliferation in normal, hyperplastic, and neoplastic human prostate

Abstract: The relative distribution pattern of the pan-endocrine marker Chromogranin A (Chr A) and the proliferation-associated Ki-67 antigen was investigated in 20 prospectively sampled prostatectomy specimens. In cryostat sections, the Chr A immunoreactivity showed evidence of endocrine differentiation in all 15 prostatic adenocarcinomas. Nine tumors displayed a weak, 5 a moderate, and 1 adenocarcinoma a strong endocrine differentiation. These findings highlight the importance of endocrine differentiation in prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(117 citation statements)
references
References 13 publications
3
111
1
2
Order By: Relevance
“…NE differentiation in prostate adenocarcinoma is usually manifested as isolated foci or islands of cells expressing certain NE-related products (23). Using double label techniques in human tissue, Bonkhoff et al (5,6) reported that increased proliferation in exocrine cells surrounded NE tumor cells. Peptide growth factors and cytokines, operating either within the context of androgen-dependent signaling mechanisms or in an androgen-independent context, are likely to be critical to the process of prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NE differentiation in prostate adenocarcinoma is usually manifested as isolated foci or islands of cells expressing certain NE-related products (23). Using double label techniques in human tissue, Bonkhoff et al (5,6) reported that increased proliferation in exocrine cells surrounded NE tumor cells. Peptide growth factors and cytokines, operating either within the context of androgen-dependent signaling mechanisms or in an androgen-independent context, are likely to be critical to the process of prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant neoplasia of the prostate with NE differentiation has poorer prognosis (35% survival rate in 2 years) compared with cases without it (97% survival rate in 2 years; Refs. 5,6). Histological studies reveal that NE cells are significantly more abundant in cancerous than in noncancerous tissues (7).…”
Section: Introductionmentioning
confidence: 99%
“…These neuroendocrine features include the appearance of neuroendocrine cell foci surrounded by proliferating epithelial cells (3). Because neuroendocrine prostate cells in normal, hyperplastic, or cancerous tissue secrete many neuropeptides with mitogenic activities like parathyroid hormone-related peptide, calcitonin, or gastrin-related peptides, it has been proposed that paracrine secretion of neurosecretory products released by neuroendocrine cells could be responsible for the progression of cancer toward an androgen-independent stage (for review, see Ref.…”
Section: From the Inserm U800 Laboratoire De Physiologie Cellulairementioning
confidence: 99%
“…They express prostate-specific antigen (PSA) (Aprikian et al, 1993;Cohen et al, 1992) and are believed to represent a third epithelial type originating from a common stem cell. As these cells do not appear to proliferate (Bonkhoff et al, 1991), it is assumed that the increased numbers seen in the tumours originate from prostatic carcinoma cells which are induced to undergo neuroendocrine differentiation. Prostatic neuroendocrine cells lack androgen receptor and it has been suggested that they could represent an androgen-insensitive cell population that can expand in some cases to populate the tumour (Krijnen et al, 1993 (Chaudhry et al.…”
Section: Immunocytochemical Analysismentioning
confidence: 99%